Quantum cascade photon ratchets for intermediate band solar cells - Curtin,OJ; Yoshida,M; Pusch,A; Hylton,NP; Ekins-Daukes,NJ; Phillips,CC; Hess,O (IEEE Journal of Photovoltaics, 2016)
We propose an antimonide-based quantum cascade design to demonstrate the ratchet mechanism for incorporation into the recently suggested photon ratchet intermediate-band solar cell. We realize the photon ratchet as a semiconductor heterostructure in which electrons are optically excited into an intermediate band and spatially decoupled from the valence band through a type-II quantum cascade. This process reduces both radiative and nonradiative recombination and can thereby increase the solar cell efficiency over intermediate-band solar cells. Our design method uses an adaptive simulated annealing genetic algorithm to determine the optimum thicknesses of semiconductor layers in the quantum cascade, allowing efficient transport (via phonon emission) of the electrons away from the interband active region.